2021
DOI: 10.1186/s12864-021-07932-4
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of apoptotic- and cell survival-related gene pathways following exposures of western corn rootworm to B. thuringiensis crystalline pesticidal proteins in transgenic maize roots

Abstract: Background Resistance of pest insect species to insecticides, including B. thuringiensis (Bt) pesticidal proteins expressed by transgenic plants, is a threat to global food security. Despite the western corn rootworm, Diabrotica virgifera virgifera, being a major pest of maize and having populations showing increasing levels of resistance to hybrids expressing Bt pesticidal proteins, the cell mechanisms leading to mortality are not fully understood. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 157 publications
(198 reference statements)
1
17
0
Order By: Relevance
“…Multiple metabolic pathways associated with significantly altered metabolites in the susceptible and resistant insects were identified. Our results are consistent with recent similar toxicogenomics studies conducted on WCR larvae fed Bt proteins or Bt-expressing maize which reported elevated transcriptional levels of cellular pathways associated with stress, detoxification, free radical damage repair, apoptosis, autophagy, repair pathways, and ABC transporters (Cry3Bb1 and Gpp34/Tpp35Ab1 50 , eCry3.1Ab 33 , Cry3Bb1 32 , Gpp34Ab1, Tpp35Ab1 and Gpp34/TppAb1 51 ). Validation of hypotheses generated with toxicometabolomic methods will require additional experimentation to determine which, if any, of the metabolites participate in WCR intoxication by Bt toxins.…”
Section: Discussionsupporting
confidence: 93%
“…Multiple metabolic pathways associated with significantly altered metabolites in the susceptible and resistant insects were identified. Our results are consistent with recent similar toxicogenomics studies conducted on WCR larvae fed Bt proteins or Bt-expressing maize which reported elevated transcriptional levels of cellular pathways associated with stress, detoxification, free radical damage repair, apoptosis, autophagy, repair pathways, and ABC transporters (Cry3Bb1 and Gpp34/Tpp35Ab1 50 , eCry3.1Ab 33 , Cry3Bb1 32 , Gpp34Ab1, Tpp35Ab1 and Gpp34/TppAb1 51 ). Validation of hypotheses generated with toxicometabolomic methods will require additional experimentation to determine which, if any, of the metabolites participate in WCR intoxication by Bt toxins.…”
Section: Discussionsupporting
confidence: 93%
“…Regardless, 50 P450s were predicted with a majority being up-regulated (78%) or putatively belonging to clan CYP6. Interestingly, 22 were shared in comparisons of maize with other plant exposure and starvation treatments, where such shared expression was previously attributed to general D. v. virgifera stress responses [64]. The arthropod cytochrome P450 family is comprised of 6 clans involved in oxidation of a variety of endogenous and exogenous substrates [128,129].…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, although only 17 ABC transporters were among the DEGs across all treatment comparisons to maize at 12-h exposure, 15 (88.2%) were ABCC members. Functional characterization of these genes will be required to determine any importance in response to consumption of different plant materials, or general stress responses of D. v. virgifera as hypothesized earlier [64].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations